An International High Court for Scientific Debates is Now Required - Gurevitz, Michael (European Journal of Applied Sciences, 2023)
The borderline of ethics in science is often unclear and occasionally questionable. Over-ambition in a highly competitive scientific environment may not only lead to great discoveries, but also to fraudulence as public recognition, promotion or rewards are tempting. To better control the authenticity and trueness of scientific output, a protecting system that involves the entire scientific community has long ago been established and is still operative nowadays.